Comparaison des performances d'élevage et de la vitalité de naissain d'huîtres creuses Crassostrea Gigas, en 3 sites du Morbihan (Rivière d'Auray et Baie de Quiberon), de mai 1999 à mars 2000 - Mazurie, Joseph; Fleury, Pierre-gildas; Claude, Serge; Hirata, Toshio; Langlade, Aime; Martin, Anne-genevieve; North, Benjamin (2000)
Summer mortalities of young oysters have been studied in 1999 through the monitoring of a unique oyster batch distributed among 3 sites located from upstream of an estuary (Fort-Espagnol, Auray river) to downstream (Kerpenhir, Auray river) up to open bay (Men er Roué, Bay of Quiberon). Mortality and growth have been monitered in parallel with vitality indices, so as to try or identify periods of weakness of oysters. The spat grew from a mean weight of 3 g, in the beginning of May to around 35 g in November, without sharp differences between sites. The summer mortalities remained moderate (10 %) in the 2 most marine stations, whereas a light peak of mortality (15 %) was recorded in July in the most continental station. Any of the physico-chemical parameters may be considered very stressful or lethal, but a wider amplitude of variation is recorded upstream. Valve movements records surprisingly reveal a closure duration identical in subtidal an intertidal sites, (around 4 to 5 hours a day, as an average), and also numerous simultaneous closures, that do not find any explanation in the water quality parameters measured. As for discontinuous measurements of physiological indicators, both muscle force and « salt loss in freshwater » show a seasonal pattern and inter-sites differences, but no clear discrimination between sites according to mortalities (probably because of the low levels of mortality). La question des mortalités estivales de naissain d'huîtres creuses en rivière d'Auray et baie de Quiberon a été abordée en 1999 par le suivi d'un lot de juvéniles mis en dans 3 stations de types bien différenciés d'amont en aval: - une station très estuarienne, au centre de la rivière d'Auray (Fort-Espagnol) - une station mi-estuarienne mi-marine, au sortir de la rivière d'Auray sur la baie de Quiberon (Kerpenhir) - une station marine en baie de Quiberon (Men-er-Roué). La mortalité et la croissance ont été suivies à des indices de vitalité afin de discerner d'éventuelles de des animaux. Le naissain est de 3 g début mai ...